Development of an evidence-informed recommendation guide to facilitate physical activity counseling between oncology care providers and patients in Canada. Issue 4 (16th February 2021) - Fong, Angela J; Sabiston, Catherine M; Nadler, Michelle B; Sussman, Jonathan; Langley, Hugh; Holden, Rachel; Stokes-Noonan, Michaela; Tomasone, Jennifer R
Abstract: Decision support aids help reduce decision conflict and are reported as acceptable by patients. Currently, an aid from the American College of Sports Medicine exists to help oncology care providers advise, assess, and refer patients to physical activity (PA). However, some limitations include the lack of specific resources and programs for referral, detailed PA, and physical function assessments and not being designed following an international gold standard (Appraisal of Guidelines for Research and Evaluation [AGREE] II). This study aimed to develop a recommendation guide to facilitate PA counseling by assessing the risk for PA-related adverse events and offering a referral to an appropriate recommendation. Recommendation guide development followed AGREE II, and an AGREE methodologist was consulted. Specifically, a stakeholder group of oncology care providers and cancer survivors were engaged to develop the assessment criteria for comorbidities, PA levels, and physical function. Assessment criteria were developed from published PA interventions, consultations with content experts, and targeted web-based searches for cancer-specific PA programs. Feedback on the recommendation guide was solicited from stakeholders and external reviewers with relevant knowledge and clinical experience. Independent AGREE methodologists appraised the development process. The recommendation guide is a five-page document, including a preamble, assessment criteria for absolute contraindications to PA, comorbidities, and PA/functional capacity with a list of appropriate resources. Independent AGREE methodologists rated the development process as strong and recommended the guide for use. The recommendation guide has the potential to facilitate PA counseling between oncology care providers and cancer survivors, thus, potentially impacting PA behavior. Abstract : A recommendation guide was rigorously developed to help oncology care providers with physical activity counselling among their patients with cancer. Lay Summary: Following a cancer diagnosis, exercise has important health benefits for cancer survivors. Sadly, most cancer survivors do not exercise at levels to gain these important benefits. Oncology care providers, such as oncologists, nurses, and allied health professionals, play an important role in health behaviors of their cancer survivor patients. We thought that they would be the best individuals to promote exercise. However, oncology care providers face barriers for discussing exercise with their patients. For example, they may not be aware of the current science, experience low confidence when discussing exercise, or not be aware of the types of available resources. We developed a short guide with the goal of assisting oncology care providers while discussing exercise with cancer survivors. The guide was developed with research scientists, oncology care providers, and cancer survivors. We followed the strict process outlined by an international guideline development protocol and included relevant science, and the guide was evaluated by experts. The guide helps the oncology care provider to find an appropriate exercise resource for the cancer survivor, such as a class, informational booklet, or website. Our next steps are to test the guide in clinics to determine whether it works for both oncology care providers and cancer survivors.